PENGARUH GROWTH, PROFITABILITAS, UKURAN PERUSAHAAN TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN - Tasya Oktari; Antoni Antoni (Fakultas Ekonomi dan Bisnis Universita Wijaya Putra Surabaya, 2023)
This study aims to prove the effect of company growth (growth) with the Total Asset Growth indicator, profitability with the Return On Assets indicator, and company size with the Firm Size (ln total assets) indicator on dividend policy with the DPR indicator in manufacturing companies in the food and beverage sub-sector. registered on the BEI in 2019-2021. This type of causal research with a quantitative method approach. The population is manufacturing companies in the food and beverage sub-sector that are listed on the BEI in 2019-2021. This study determines the sample purposive sampling method. So that a total of 54 samples were obtained in this study. This study uses multiple linear analysis methods: (1) Growth has a significant effect (2) Profitability has a significant effect (3) Firm size has no significant effect (4) Growth, Profitability, Firm Size have a simultaneous effect.